The Relationship of Parenting and Juvenile Delinquency Rate in Flats - Nihayati, Hanik Endang; Sholihah, Nadia Nur Mar'atush; Qonaah, Arina Qonaah1 (International Journal of Psychosocial Rehabilitation, 2020)
The increase in the number of juvenile delinquents in flats can be dangerous for the future of adolescents. One of the factors causing this is parents. This study aims to determine the relationship of parenting parents with juvenile delinquency levels in flats. The design of this study was cross-sectional. Analysis of the study was Carried out using the chi-square test. The number of samples in this study was 110 teenagers in flats with purposive sampling. The dependent variable was juvenile delinquency. The questionnaire from The Parenting Style and Dimension Questionnaire (PSDQ) and a juvenile delinquency questionnaire. The most parenting style at low delinquency level is democratic parenting (5.4%), parenting style at medium delinquency level is authoritarian parenting (32.4%), permissive delinquency parenting at high levels (62.2%). There is a relationship between parenting with juvenile delinquency levels with p = 0.001. There is a relationship between parenting with the level of juvenile delinquency in flats. Therefore health workers can carry out adolescent posts to reduce juvenile delinquency in flats.